The guide to investigation of mouse pregnancy - Croy, B. A. (B. Anne); Yamada, Aureo T.; DeMayo, Francesco J.; Adamson, S. Lee, 1954-; ScienceDirect eBooks (Amsterdam : Elsevier/Academic Press, 2014)
"The Guide to Investigation of Mouse Pregnancy is the first publication to cover the mouse placenta or the angiogenic tree the mother develops to support the placenta. This much-needed resource covers monitoring of the cardiovascular system, gestational programming of chronic adult disease, epigenetic regulation, gene imprinting, and stem cells. Offering detailed and integrated information on how drugs, biologics, stress, and manipulations impact pregnancy in the mouse model, this reference highlights techniques used to analyze mouse pregnancy"--Publisher's description.
Part I: Atlas. The cycling and pregnant mouse: gross anatomy -- Implant site dissections -- Microscopic anatomy of the pregnant mouse uterus throughout gestation -- Anatomy of the mouse placenta throughout gestation -- Whole-mount immunohistochemistry of early implantation sites -- Magnetic resonance imaging of the mouse placenta -- Part II: Basic biology. Reproductive tract changes during the mouse estrous cycle -- First cell fate decisions in early development: towards establishment of the trophoblast lineage -- Tetraploid complementation assay -- Biology of the ectoplacental cone -- Decidualization and endometrial extracellular matrix remodeling -- Postimplantation development of the chorioallantoic placenta -- Unique features of endometrial dynamics during pregnancy -- Pathology analysis of the placenta -- Changes in structures and relationships of trophoblasts, leukocytes, and maternal vessels in implantation sites to midpregnancy -- The uteroplacental, fetoplacental, and yolk sac circulations in the mouse -- Physiological exchange across mouse placenta -- Hypoxia-associated regulation within implantation sites -- Leukocyte population dynamics and functions at the maternal--fetal interface -- In vivo tracking of mononuclear cells in the virgin uterus and in implantation sites -- Microchimerism in mouse pregnancy -- Systems biology analyses of the placenta -- Contribution of placental genomic imprinting and identification of imprinted genes -- Epigenetics of placental development and function -- Genome-wide analysis of the mouse deciduoma -- Conditional gene deletion in the placenta using the Cre-loxP system -- Genetic engineering of mice to investigate uterine function in early pregnancy -- Lentivirus-mediated transduction of optical reporter genes in blastocysts for placental studies -- Blood pressure regulation during mouse pregnancy -- Intravital imaging of vasoactivity in the uterine arterial tree during pregnancy -- Multimodal imaging of the mouse placenta -- Regulation of parturition -- Cervical changes accompanying birth -- Peri-partum changes to mouse pubic symphysis -- Mammary gland morphogenesis and function during pregnancy -- Gestational programming of the cardiovascular system -- Maternal stress-mediated gene expression changes in the mouse placenta: a mosaic hypothesis of epigenesis -- Pregnancy alterations from environmental pollutants -- Part III: Protocols. Monitoring mouse estrous cycles -- Lentivirus transduction of gene tags in blastocysts -- Tetraploid complementation assay -- Pseudopregnant bead-induced mouse deciduoma model -- Ectoplacental cone isolation, culture and assessment -- Layer-enriched tissue dissection of the mouse placenta in late gestation -- Protocols for placental histology -- Best practice for quantifying the microscopic structure of mouse placenta: the stereological approach -- Electron microscopy and immunoelectromicroscopy protocols -- Laser capture microdissection -- Immunofluorescence and immunohistochemistry -- Nonradioactive in situ hybridization: optimization for tissue sections from pregnant uteri and placenta during the first half of pregnancy -- Whole mount in situ immunohistochemistry -- Guidelines for evaluation of reproductive and developmental endpoints -- Flow cytometric analysis of myometrial and decidual cell suspensions -- Uterine leukocyte isolation and culture -- Scanning electron microscopy and micro-computed tomography imaging of the utero- and fetoplacental circulations -- Radiotelemetry in mouse pregnancy -- Ex vivo perfusion of the mouse placenta for maternal--fetal interaction studies during pregnancy -- Evaluation of placental transport function -- Hypoxia-associated regulation within implantation sites -- Method to locate the uterine artery in mice for micro-ultrasound doppler blood velocity examination -- Two-photon intravital microscopy of the virgin and pregnant mouse uterus -- Intravital imaging of vasoactivity in the uterine arterial vasculature tree during pregnancy -- MRI, intra-vital, and ex-vivo fluorescence microscopy of the mouse uterine vasculature and placenta -- Assessment of changes in the peripartum cervix -- Pubic symphysis evaluation -- Labor and preterm labor -- Epithelial transplantation into the cleared mammary fat pad -- Dietary and hypoxic protocols that alter placental gene expression in response to maternal stress -- Parental-specific gene expression and epigenetic analyses of imprinted genes in mouse placenta -- A method for obtaining epigenomic data -- Methods for genetic engineering in mice -- Appendix: reproductive parameters of common, commercially available mouse strains.
Online resource; title from resource home page (ebrary, viewed March 7, 2016).
Includes bibliographical references and index.
Elsevier
Keywords: Mice -- Pregnancy; Mice -- Reproduction; MEDICAL -- Physiology; SCIENCE -- Life Sciences -- Human Anatomy & Physiology; Animals; Female; Mice; Placenta; Pregnancy; Electronic books